PEMBUATAN GAME 2D MULTIPLAYER SHOOTING “BERZEKER’S TRIAL” PADA PLATFORM PC - Donny Kurniawan; Jeanny Pragantha; Darius Andana Haris (Jurnal Ilmu Komputer dan Sistem Informasi, 2020)
“Berzeker Trial” is a 2D multiplayer game for PC. In this game, players are acted as special force. Their objective is to defeat General Evil using their weapon. This game is created by Unity engine and C# programming language. Also, this game only compatible with XBOX 360 Controller as the main controller. This game is tested by many methods i.e. blackbox test, alpha test by the lecturers and, beta testing by 31 respondens. The con